BIOLOGICAL EFFECTIVENESS OF FIX GOLD 70% W.D.G. AGAINST APPLE SCAB - B.S. Sodiqov (European Journal of Agricultural and Rural Education, 2024)
Scab is one of the most common diseases in apple orchards, the fight against which is always expensive. Untimely control of this disease leads to serious crop losses and a decrease in the quality of harvested fruits. Currently, the strategy for protecting apples from scab is based on repeated applications of fungicides. In this article, lock in gold 70% w.d.g. The results of our research on the use of fungicide are presented. According to the results of our research, Fix Gold 70% w.d.g. has the greatest biological effectiveness. In the variant treated with the norm, a fungicide consumption of 0.8 kg/ha was observed. In particular, in the leaf it was 89.77%, in the branch 87.01% and in the fruit 89.02%. Disease development was 1.8% in the leaf, 2.0% in the branch and 1.8% in the fruit.